2019
DOI: 10.1155/2019/5705039
|View full text |Cite
|
Sign up to set email alerts
|

Role of 99mTc-HIDA Scan for Assessment of Gallbladder Dyskinesia and Comparison of Gallbladder Dyskinesia with Various Parameters in Laparoscopic Cholecystectomy Patients

Abstract: Objectives. Pathogenesis of gallstone includes bile stasis due to defect in the gallbladder muscle contraction. Our aim of the study is to find out the role of 99mTc-HIDA scan in assessment of gallbladder dyskinesia in cholelithiasis patients before laparoscopic cholecystectomy and compare the gallbladder dyskinesia with various parameters like symptoms of patients, diabetic status of patients, gallstones size and number, and cholecystitis features in histopathology report after surgery. Material and Method. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…It is a useful tool for diagnosis of dyskinesia, small and multiple stones before surgery, but also could have some importance after surgery to diagnose some bile problems. 12 In the case of the patient, a minimal amount of bile leakage is shown; however, she did not require treatment at that time, so she was discharged and controlled in 1 week.…”
Section: Case Descriptionmentioning
confidence: 84%
“…It is a useful tool for diagnosis of dyskinesia, small and multiple stones before surgery, but also could have some importance after surgery to diagnose some bile problems. 12 In the case of the patient, a minimal amount of bile leakage is shown; however, she did not require treatment at that time, so she was discharged and controlled in 1 week.…”
Section: Case Descriptionmentioning
confidence: 84%
“…Among the many common complications of bariatric surgery, increased gastric motility manipulates GI hormone production [ 10 ]. The hormone of focus in this study is CCK, which is secreted by duodenal I cells in response to gastric emptying and leads to gallbladder contraction and relaxation of the sphincter of Oddi [ 5 ]. However, this hormone also delays gastric emptying in persons with increased gastric motility.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, we use cholecystokinin 99m technetium-labeled hepatoiminodiacetic acid (99mTc-HIDA (CCK-HIDA)) for the patient’s workup as studies have shown it is the most accurate modality for diagnosing gallbladder disease by determining gallbladder contractility and ejection fraction (EF) [ 5 ]. Gallbladder hypomotility also known as biliary dyskinesia is a common functional biliary disorder defined by an EF of less than 35% on a 99mTc-HIDA (CCK-HIDA) scan [ 6 ].…”
Section: Introductionmentioning
confidence: 99%